2010
DOI: 10.1103/physrevb.82.060510
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic ordering induced by paramagnetic depairing in unconventional superconductors

Abstract: Antiferromagnetic ͑AFM͒ ͑or spin-density wave͒ quantum critical fluctuation enhanced just below H c2 ͑0͒ have been often observed in d-wave superconductors with a strong Pauli paramagnetic depairing ͑PD͒ including CeCoIn 5 . It is shown here that such a tendency of field-induced AFM ordering is a consequence of strong PD and should appear particularly in superconductors with a gap node along the AFM modulation. Two phenomena seen in CeCoIn 5 , the AFM order in the Fulde-Ferrell-Larkin-Ovchinnikov ͑FFLO͒ state … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 31 publications
5
66
0
Order By: Relevance
“…Prior to this recent experimental evidence, it was suggested [6][7][8] that the Fulde-Ferrel Larkin-Ovchinnikov (FFL0) state 9,10) occurs in the HFLT region, with finite momentum pairing created by the strength of the Pauli limit. Recent theoretical studies emphasize the key role of the Pauli depairing of the Cooper pairs 11) and the possibility of a staggered field induced triplet component associated with the appearance of an AF phase coupled with or without a FFLO state 12,13) Here we report on detailed magnetization M (T, H) experiments with the field H aligned along the c axis of the tetragonal crystal in order to search where are the singularities in the field dependence of the Sommerfeld coefficient γ of the specific heat and to determine if signatures of such a Q-phase are also present for this direction. For H along the c axis it was also suggested that H c2 (0) corresponds to an AF quantum critical point.…”
Section: 2)mentioning
confidence: 99%
“…Prior to this recent experimental evidence, it was suggested [6][7][8] that the Fulde-Ferrel Larkin-Ovchinnikov (FFL0) state 9,10) occurs in the HFLT region, with finite momentum pairing created by the strength of the Pauli limit. Recent theoretical studies emphasize the key role of the Pauli depairing of the Cooper pairs 11) and the possibility of a staggered field induced triplet component associated with the appearance of an AF phase coupled with or without a FFLO state 12,13) Here we report on detailed magnetization M (T, H) experiments with the field H aligned along the c axis of the tetragonal crystal in order to search where are the singularities in the field dependence of the Sommerfeld coefficient γ of the specific heat and to determine if signatures of such a Q-phase are also present for this direction. For H along the c axis it was also suggested that H c2 (0) corresponds to an AF quantum critical point.…”
Section: 2)mentioning
confidence: 99%
“…[4][5][6] Furthermore, an antiferromagnetic phase has been observed under high magnetic fields in the basal plane, but only inside the superconducting mixed state. [7][8][9][10] CeCoIn 5 is also easily turned antiferromagnetic upon Rh doping, 11) as well as Cd 12) and Hg 13) doping. And back in 2003, it was already discovered by two groups 14,15) that for fields parallel to the c-axis, the range of existence of the Fermi liquid regime seemed to shrink on approaching H c2 (0) from the high field region, pointing to a possible QCP in the immediate vicinity of that field.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most peculiar properties of this phase is that the AF order does not extend into the normal state and exists only in the SC state [21], suggesting some additional stabilization of AF order by the SC state. Some theories proposed mechanisms for stabilizing AF order due to strong Pauli-limiting and a nodal SC gap structure, without a FFLO state [22,23], while in another theory, a coexisting FFLO state is necessary for the formation of AF order [24]. A recent In-NMR study for fields along [100] has suggested the formation of a pure FFLO phase leading to an anomalous line broadening already at fields between 9.2 T and H HFLT = 10.3 T, while the coexistence of AF order and FFLO superconductivity is claimed at H HFLT ≤ H ≤ H c2 [25].…”
mentioning
confidence: 99%